Enriched Environment and Exercise Enhance Stem Cell Therapy for Stroke, Parkinson’s Disease, and Huntington’s Disease - Berlet, Reed; Galang Cabantan, Dorothy Anne; Gonzales-Portillo, Daniel; Borlongan, Cesar V. (Frontiers in Cell and Developmental Biology, 2022)
Stem cells, specifically embryonic stem cells (ESCs), mesenchymal stem cells (MSCs), induced pluripotent stem cells (IPSCs), and neural progenitor stem cells (NSCs), are a possible treatment for stroke, Parkinson’s disease (PD), and Huntington’s disease (HD). Current preclinical data suggest stem cell transplantation is a potential treatment for these chronic conditions that lack effective long-term treatment options. Finding treatments with a wider therapeutic window and harnessing a disease-modifying approach will likely improve clinical outcomes. The overarching concept of stem cell therapy entails the use of immature cells, while key in recapitulating brain development and presents the challenge of young grafted cells forming neural circuitry with the mature host brain cells. To this end, exploring strategies designed to nurture graft-host integration will likely enhance the reconstruction of the elusive neural circuitry. Enriched environment (EE) and exercise facilitate stem cell graft-host reconstruction of neural circuitry. It may involve at least a two-pronged mechanism whereby EE and exercise create a conducive microenvironment in the host brain, allowing the newly transplanted cells to survive, proliferate, and differentiate into neural cells; vice versa, EE and exercise may also train the transplanted immature cells to learn the neurochemical, physiological, and anatomical signals in the brain towards better functional graft-host connectivity.